Do clinical features of Lesch‐Nyhan disease correlate more closely with hypoxanthine or guanine recycling?. Issue 1 (12th June 2015) - Schretlen, David J.; Callon, Wynne; Ward, Rebecca E.; Fu, Rong; Ho, Tiffany; Gordon, Barry; Harris, James C.; Jinnah, H. A.
Abstract: Lesch‐Nyhan disease (LND) is a rare, X‐linked recessive neurodevelopmental disorder caused by deficiency of hypoxanthine‐guanine phosphoribosyltransferase (HGprt), an enzyme in the purine salvage pathway. HGprt has two functions; it recycles hypoxanthine and guanine. Which of these two functions is more relevant for pathogenesis is unclear because some evidence points to hypoxanthine recycling, but other evidence points to guanine recycling. In this study, we selectively assayed hypoxanthine (Hprt) and guanine (Gprt) recycling in skin fibroblasts from 17 persons with LND, 11 with an attenuated variant of the disease (LNV), and 19 age‐, sex‐, and race‐matched healthy controls (HC). Activity levels of both enzymes differed across groups (p < 0.0001), but only Gprt distinguished patients with LND from those with LNV (p < 0.05). Gprt also showed slightly stronger correlations than Hprt with 13 of 14 measures of the clinical phenotype, including the severity of dystonia, cognitive impairment, and behavioral abnormalities. These findings suggest that loss of guanine recycling might be more closely linked to the LND/LNV phenotype than loss of hypoxanthine recycling.